Indonesia DAMPAK DIGITAL MARKETING DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN CUSTOM CAKE DI KOTA BANDUNG - Fransiscus Duran; Yolla Margaretha (Value : Jurnal Manajemen dan Akuntansi, 2023)
In this Digital Era, online marketing has become one of the most effective strategies in reaching potential markets through promotional media, including the custom cake business. The development of this business through the marketplace is one of the important strategies in increasing sales and expanding potential market share. The purpose of this research is to study how promotion and digital marketing influence consumer decisions to buy homemade cakes in Bandung City. This quantitative research was conducted in the Bandung City area using the Cluster Random Sampling Technique. A total of 100 respondents filled in the data and the data was collected through an online questionnaire and analyzed using SPSS version 26, through testing Validity, Reliability, Normality and Multiple Linear Regression Tests. The results show that the use of digital marketing and promotion influences customer decisions in Bandung City to buy Custom Cake. This research can be used by Custom Cake Companies to increase interest in buying custom cakes by conducting promotions and also through digital marketing.